2018
DOI: 10.1002/bjs.10756
|View full text |Cite
|
Sign up to set email alerts
|

Clinicopathological, genomic and immunological factors in colorectal cancer prognosis

Abstract: Background: Numerous factors affect the prognosis of colorectal cancer (CRC), many of which have long been identified, such as patient demographics and the multidisciplinary team. In more recent years, molecular and immunological biomarkers have been shown to have a significant influence on patient outcomes. Whilst some of these biomarkers still require ongoing validation, if proven to be worthwhile they may change our understanding and future management of CRC. The aim of this review was to identify the key p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
50
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 42 publications
(51 citation statements)
references
References 86 publications
0
50
0
1
Order By: Relevance
“…Over the last several decades, our knowledge of the complex relationship between clinicopathological characteristics, genomic, and immunological features that determine prognosis among patients with CC has increased . Even though molecular biomarkers (ie, gene expression, signaling pathways, and protein expression) and immunological factors (ie, neutrophil/lymphocyte ratio, immune infiltrate [Immunoscore®]) may be useful in guiding treatment decisions, epidemiological studies have demonstrated that patient demographics and “classic” clinicopathological characteristics may also be important predictors of outcomes among patients with CC . In addition, while genetic‐based targeted cancer therapy is emerging, histological tumor subtyping is more readily available in the vast majority of clinical settings .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Over the last several decades, our knowledge of the complex relationship between clinicopathological characteristics, genomic, and immunological features that determine prognosis among patients with CC has increased . Even though molecular biomarkers (ie, gene expression, signaling pathways, and protein expression) and immunological factors (ie, neutrophil/lymphocyte ratio, immune infiltrate [Immunoscore®]) may be useful in guiding treatment decisions, epidemiological studies have demonstrated that patient demographics and “classic” clinicopathological characteristics may also be important predictors of outcomes among patients with CC . In addition, while genetic‐based targeted cancer therapy is emerging, histological tumor subtyping is more readily available in the vast majority of clinical settings .…”
Section: Discussionmentioning
confidence: 99%
“…To better account for any residual confounding due to different clinicopathological characteristics of patients with CA, MUC, and SC cancers, a sensitivity analysis to investigate the association of histological subtype with OS was performed within matched cohorts decisions, epidemiological studies have demonstrated that patient demographics and "classic" clinicopathological characteristics may also be important predictors of outcomes among patients with CC. 21 In addition, while genetic-based targeted cancer therapy is emerging, histological tumor subtyping is more readily available in the vast majority of clinical settings. [24][25][26][27] In turn, many patients may benefit from personalized treatment based on the histological tumor subtyping.…”
Section: Propensity Score Matching Analysesmentioning
confidence: 99%
“…These cells are playing a fateful role in tumor progression through a complex interaction with all other components of TME. However, those interactions are still convoluted and argumentative issues were reported on it [11,12]. The association of immune system activity and prognosis in CRC was described for a long time [13].…”
Section: Introductionmentioning
confidence: 99%
“…Profiling of both solid and hollow organ tumours follows on the heels of the remarkable advances in gastrointestinal stromal tumours and breast cancer. Will genomics and related fields unravel the challenges to prognosis and treatment of colorectal cancer? The fact that there are molecular targets to enhance responses to radiotherapy opens the possibility of more widespread organ preservation in rectal cancer.…”
mentioning
confidence: 99%
“…It should not surprise us that one of our most bacteria‐rich environments houses elements that prove noxious under the stressed circumstances of malignancy and surgical trauma. The challenges this represents are illustrated beautifully in this issue, as are the up‐to‐date, key pathological variables that should be determined for all patients with colorectal cancer for optimal, multidisciplinary, individualized care.…”
mentioning
confidence: 99%